Higher Childhood Red Meat Intake Frequency Is Associated with Earlier Age at Menarche–3. Issue 4 (9th March 2016) - Jansen, Erica C; Marín, Constanza; Mora-Plazas, Mercedes; Villamor, Eduardo
Abstract: Background: Early age at menarche is associated with increased breast cancer risk. Red meat consumption in adolescence predicts breast cancer risk, but it is unknown whether it is also related to earlier menarche. Objective: We studied the association between intake of red meat at ages 5–12 y and age at menarche in a prospective study. Methods: We assessed usual diets with a food-frequency questionnaire in a group of 456 girls aged 8.4 ± 1.7 y and followed them for a median 5.6 y in Bogotá, Colombia. Girls were asked periodically about the occurrence and date of menarche. Median age at menarche was estimated with use of Kaplan-Meier survival probabilities by categories of red meat intake frequency. Cox proportional hazards models were used to compare the incidence of menarche by red meat intake frequency, adjusting for potential sociodemographic and dietary confounders including total energy intake and intake frequency of other animal food groups (dairy, poultry, freshwater fish, tuna/sardines, eggs, and innards). Results: Median age at menarche was 12.4 y. After adjustment for total energy intake, maternal parity, and socioeconomic status, red meat intake frequency was inversely associated with age at menarche. When compared with girls with red meat intake <4 times/wk, those consuming it ≥2 times/d had a significantly earlier age at menarche (HR: 1.64; 95% CI: 1.11, 2.41; P -trend = 0.0009). Incidentally, we found that girls with tuna/sardine intake >1 time/wk had a significantly later age at menarche (HR: 0.62; 95% CI: 0.42, 0.90; P = 0.01) than those with intake <1 time/mo. Intake frequency of other animal food groups was not significantly associated with age at menarche. Conclusion: Higher red meat intake frequency during childhood is associated with an earlier age at menarche, whereas greater fatty fish intake frequency is associated with a later menarcheal age.